If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -4(-6x + 17) = 142 Reorder the terms: 6x + -4(17 + -6x) = 142 6x + (17 * -4 + -6x * -4) = 142 6x + (-68 + 24x) = 142 Reorder the terms: -68 + 6x + 24x = 142 Combine like terms: 6x + 24x = 30x -68 + 30x = 142 Solving -68 + 30x = 142 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '68' to each side of the equation. -68 + 68 + 30x = 142 + 68 Combine like terms: -68 + 68 = 0 0 + 30x = 142 + 68 30x = 142 + 68 Combine like terms: 142 + 68 = 210 30x = 210 Divide each side by '30'. x = 7 Simplifying x = 7
| -14=-4+5u | | 4x-3(-x-2)=69 | | 2y^2+y=1+y+y^2 | | 5x+2(4x-6)=92 | | 1+-3f=4 | | 7=(3+b)4 | | 6(k-4)-8=9k+7 | | 3-9x=-7(x+5) | | 3x+7(3x-12)=132 | | -1=2w+5 | | 5x+3(x-15)=35 | | 7x+3(7x-6)=150 | | 5x-3(x-5)=-3+4x+14 | | (x+6)=6(x+9) | | 3x+2(7x-6)=73 | | 9x=50000 | | 6x+3(4x-18)=162 | | 8y+12=7x+4 | | 3x+2(x+6)=67 | | 2x-3(4x+5)=-6(x-3)-1 | | y=0.15x+29 | | (5x+12)=180-3x | | 2b-34=54 | | 8=2r-2 | | 2b+3=54 | | 3(2a-6)=8(2a-3) | | 5x-0.1=0.5x-1 | | y-3=.4(x-2) | | 86=4w+10 | | 2-5(-4+5-2X)=-25x+38 | | (z-9)(z-3)=0 | | 2y^2-y=1 |